Incidence of pressure injuries in hospitalized patients: A literature review (International Seven Journal of Health Research, 2023)
The skin is fundamental to human life as it participates in many vital organic functions. One of the most common complications affecting the integumentary system of hospitalized patients is Pressure Injury. LPP is defined as an open, intact or ulcerated lesion on the skin, soft tissues or adjacent tissues that occurs predominantly under bony prominences. This adverse event causes pain and discomfort, as well as increasing hospitalization time and consequently hospital costs. The aim of this study was therefore to analyze the incidence of PPI in hospitalized patients over the last 6 years, to describe the anatomical region most affected and the degree of injury that predominated. This is a descriptive bibliographic research carried out in 2020 in the Scientific Electronic Library Online (Scielo) and Virtual Health Library (VHL) databases. Five articles from 2013 to 2019 that met the inclusion criteria and objectives of the study were used. It was found that the lack of adherence to PPI prevention protocols corroborated the maintenance of high rates of PPI, showing that preventive actions implemented in isolation may not have the expected result in reducing the number of cases. There is a need for more studies on the incidence of PI and the use of tools such as continuing education to raise awareness of the importance of implementing protocols to prevent PI in health institutions.